Synthesis of cobalt sulfide multi-shelled nanoboxes with precisely controlled two to five shells for sodium-ion batteries - Wang, Xiao (2020)
We report the synthesis of cobalt sulfide multi-shelled nanoboxes through metal–organic framework (MOF)-based complex anion conversion and exchange processes.Thepolyvanadate ions react with cobalt-based zeolitic imidazolateframework-67 (ZIF-67) nanocubes to form ZIF-67/cobaltpolyvanadate yolk-shelled particles.The as-formed yolk-shelled particles are gradually converted into cobalt divanadatemulti-shelled nanoboxes by solvothermal treatment. Thenumber of shells can be easily controlled from 2to5byvarying the temperature.Finally,cobalt sulfide multi-shellednanoboxes are produced through ion-exchange with S2@ionsand subsequent annealing. The as-obtained cobalt sulfidemulti-shelled nanoboxes exhibit enhanced sodium-storageproperties when evaluated as anodes for sodium-ion batteries.Forexample,ahigh specific capacity of 438 mAhg@1can beretained after 100 cycles at the current density of 500 mAg@1.